A combination of Tropilaelaps mercedesae and imidacloprid negatively affects survival, pollen consumption and midgut bacterial composition of honey bee. (April 2021) - Ma, Shilong; Yang, Yang; Fu, Zhongmin; Diao, Qingyun; Wang, Mengyue; Luo, Qihua; Wang, Xing; Dai, Pingli
Abstract: Tropilaelaps mercedesae is not only a major threat to honey bees in Asia but also a potential risk to global apiculture due to trade. Imidacloprid is a systemic insecticide that negatively affects individual bees. Moreover, the health of honey bees may be threatened by imidacloprid exposure and T. mercedesae infestation. We studied the effects of T. mercedesae and imidacloprid on the survival, food consumption and midgut bacterial diversity of Apis mellifera in the laboratory . Illumina 16S rRNA gene sequencing was used to determine the bacterial composition in the honey bee midgut. T. mercedesae decreased survival in parasitized honey bees compared with nonparasitized honey bees, but there was no significant difference in food consumption. The imidacloprid 50 μg/L diet significantly decreased syrup consumption of A. mellifera compared with the control diet. The combination of T. mercedesae infestation and imidacloprid 50 μg/L exposure reduced survival and increased pollen consumption of A. mellifera . T. mercedesae infestation or a combination of T. mercedesae infestation and exposure to 25 μg/L imidacloprid affected the midgut bacterial composition of honey bees. T. mercedesae infestation and imidacloprid exposure may reduce the survival and affect honey bee health. Graphical abstract: Image 1 Highlights: Tropilaelaps mercedesae impacted Apis mellifera survival. Tropilaelaps mercedesae  and 50 μg/L imidacloprid impacted  Apis mellifera  survival and pollen consumption. Tropilaelaps mercedesae infestation affected the midgut bacterial composition of Apis mellifera. Tropilaelaps mercedesae and 25 μg/L imidacloprid affected the midgut bacterial composition of Apis mellifera.